Estudos silviculturais de uma população natural de Copaifera multijuga Hayne - Leguminosae, na Amazônia Central. 1 - Germinação - Alencar, Jurandyr da Cruz (Acta Amazonica, 1981)
The germination of Copaiba (Copaifera multijuga Hayne), from the Manaus region (Forest Reserve Ducke), was investigated in order to complete the studies on the trees oil-resin production since 1976. Seeds of 16 selected trees were studied for purity, vitality and germination. A high average germination percentage of 87.5% was obtained. Germination occured, on average, 14 days after sowing, with the total germination period oscilating between 21 - 54 days, with an average of 35 days.